Smack - Burgess, Melvin (New York : Avon Tempest, 1999)
After running away from their troubled homes, two English teenagers move in with a group of squatters in the port city of Bristol and try to find ways to support their growing addiction to heroin.
"Originally published in Great Britain in 1996 by Andersen Press Limited under the title Junk"--T.p. verso.
Keywords: Runaways -- Fiction; Heroin -- Fiction; Drug abuse -- Fiction; England -- Fiction